RANCANG BANGUN APLIKASI RESERVASI SERVICE UNTUK BENGKEL SEPEDA MOTOR BERBASIS WEB - I Gusti Ngurah Agung Widhiananda; I Made Arsa Suyadnya; Komang Oka Saputra (Program Studi Teknik Elektro UNUD, 2017)
Motorbike repair shops are one of the industries which provide services for repairs, tunings, or even providing availability of parts to the customer. Punctuality is one of the most important factor to every users that uses this kind of service. Nowadays, most of the repair shops provide several means to book and to make a reservation for most customer's intended services. But, they are done manually by the management, either by direct visits or by call. This will gradually become a tedious task and requires meticulous book keeping to track a huge numbers of reservations. This research was done as an attempt to develop a responsive web-based system, starting from its basic infrastructure analysis, built in PHP with standard MySQL database system. The result of this development is intended to cater and accommodate the needs of customers for reserving services ahead as well as to find the nearest, most suitable shops for their appointments automatically. All of this system functionalities are working as intended according to black box testing method.